Socio-Economic Mapping of Tarai Bangun Village, Tambang District, Kampar Province, Riau District - Y Rahmat Akbar (Indonesian Journal of Economics, Social, and Humanities, 2021)
This research aims to identify environmental factors and the context of vulnerability in local communities, identify social problems and illustrate the socio-economic conditions of local communities, and identify key actors and key groups in Tarai Bangun Village, Tambang District, Kampar Regency, Riau Province . The research design was carried out qualitatively and descriptively with the Rapid Rural Appraisal (RRA) approach with representative samples, in-depth interviews and observations. The results of the study, it was concluded that the parties who were the actors of the social interaction process on the village actor map explained that the village head had a central role in the community, by having a direct relationship to RW, RT, LKMD, KESRA, Posyandu. There are four main socio-economic problems, namely poverty, unemployment, juvenile delinquency and health.